Flexible composite phase-change material, preparation method and solar thermoelectric power generation system applying flexible composite phase-change material
By adding SEBS, OBC and EG to paraffin PW, a high thermal conductivity and flexible composite phase change material is formed, which solves the problems of low thermal conductivity and poor mechanical properties of phase change materials, and efficient storage and release of heat energy, and improves the solar temperature difference Continuous operation capability of power generation system.
Patent Information
- Application Number
- CN202411258389.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing phase change materials have low thermal conductivity and poor mechanical properties, making it difficult to maintain stability in complex structures and dynamic environments, resulting in local accumulation and waste of heat, and traditional materials are difficult to bend, resulting in contact thermal resistance.
By adding SEBS, OBC and EG to paraffin PW, a flexible composite phase change material is formed, which improves its thermal conductivity, flexibility and leakage resistance. The cross-linking of SEBS and OBC is used to form a continuous network structure. EG is used as a porous thermal conductivity matrix material to enhance Package performance and thermal response rate.
It achieves high thermal conductivity (3.07~4.54W/(m·K) and good flexibility, ensuring that the material stabilizes the storage and releases heat energy in complex environments, significantly improving the thermal management efficiency and the continuous operation capability of the solar temperature differential power generation system.
Smart Images

Figure CN119119748A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change heat storage materials and solar temperature difference power generation, and in particular to a flexible composite phase change material, a preparation method and a solar temperature difference power generation system using the same. Background Art
[0002] As the world's pursuit of clean energy and sustainable development increases, thermoelectric power generation technology, as an emerging green energy utilization method, is gradually gaining attention. This technology uses the temperature difference existing in nature or industrial processes to directly convert thermal energy into electrical energy through thermoelectric materials without the need for mechanical movement or fossil fuels, providing a new solution for power supply in areas where traditional power supply systems are difficult to build and maintain, and in special occasions. In particular, thermoelectric power generation technology using solar energy as a heat source has a good development prospect in distributed energy supply, outdoor power generation and other occasions.
[0003] However, solar energy has obvious discontinuous characteristics, which makes it difficult for power generation systems to operate continuously. There is an urgent need to develop efficient heat storage materials and technologies. Phase change materials, as an important energy conversion and storage medium, have shown great potential in many fields of heat storage and thermal management. Although phase change materials have many advantages in theory, their limitations cannot be ignored in practical applications. For example, the low thermal conductivity of phase change materials makes it difficult to transfer the absorbed heat to the interior of the phase change material, resulting in local accumulation and waste of heat; and traditional phase change materials often have poor mechanical properties, lack flexibility, and are difficult to bend, making it difficult for them to fully fit with the heat transfer surface, resulting in contact thermal resistance; in addition, phase change materials have high fluidity after melting, which means that in complex or dynamically changing environments, they may be difficult to remain stable and prone to deformation.
[0004] In view of the technical problem of low thermal conductivity of phase change materials, a composite phase change material with high thermal conductivity can be obtained by directly adsorbing the phase change material with a thermal conductive filler. For example, prior art 1 (Liu F, Wang J, Wang F, et al. Battery thermal safety management with form-stable and flame-retardant phase change materials [J]. International Journal of Heat and Mass Transfer, 2024, 218: 124764.) uses the porous network structure of EG as a carrier, and incorporates an environmentally friendly and non-toxic silica-based flame retardant, and melt-blends it with paraffin PW to form a composite phase change material with a thermal conductivity of 0.892W / (m·K), which is applied to battery thermal management.
[0005] In view of the technical problems that phase change materials have poor mechanical properties and lack flexibility and are difficult to bend, a flexible grid is constructed using the cross-linked structure of a flexible elastomer to achieve the flexibility of phase change materials. The development of flexible phase change materials can not only solve the shortcomings of traditional materials in structural adaptability and thermal energy utilization efficiency, but also expand their application in various complex structures and dynamic environments. The flexibility of this material will enable it to better adapt to and respond to external loads while maintaining good thermal energy storage and release capabilities, thereby optimizing thermal management and improving thermal energy utilization efficiency. For example, prior art 2 (Sun Y, Zhang N, Sun Q, et al. A novel form stable phase change material based on elastomeric copolymer and carbon nanotubes with photo-thermal conversion performance, Journal of Energy Storage, 2023, 63: 107043.) uses hydrogenated styrene-butadiene block copolymer SEBS and olefin block copolymer OBC as carrier materials, carbon nanotubes CNT as high-efficiency light-absorbing materials, and paraffin PW as PCM to prepare a shaped composite phase change material with photothermal conversion function, which has good packaging ability and flexibility. However, the material obtained by this technical solution also has the problem of low thermal conductivity, and its thermal conductivity is only 0.264W / (m·K). Summary of the invention
[0006] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a flexible composite phase change material, a preparation method and a solar temperature difference power generation system using the same.
[0007] The present invention aims to solve the technical problems existing in the prior art through the following principles:
[0008] 1. SEBS as a linear triblock copolymer has good temperature resistance and aging resistance, while OBC as a multiblock copolymer has good cross-linking effect. Through the cross-linking of OBC and SEBS, the degree of cross-linking is increased, a continuous flexible network structure is formed, the packaging performance and flexibility of the composite phase change material are improved, and the interface thermal resistance during use is reduced;
[0009] 2. Expanded graphite EG, as a carbon-based porous material, has the advantages of high thermal conductivity and rich pore structure. Adding EG to phase change materials can not only improve the thermal conductivity of phase change materials, but also play an excellent packaging role to prevent leakage of liquid phase change materials.
[0010] 3. Paraffin wax PW, as a phase change material, has the advantages of low price, high heat storage density and good stability. It is widely used in medium and low temperature phase change heat storage and temperature control fields.
[0011] Therefore, by adding SEBS, OBC and EG to paraffin wax PW, the flexibility, thermal conductivity and anti-leakage performance of the phase change material can be improved at the same time.
[0012] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0013] A flexible composite phase change material, using hydrogenated styrene butadiene block copolymer SEBS as a flexible segment, olefin block copolymer OBC as a flexible cross-linking reinforcement material, paraffin wax PW as a phase change material, and expanded graphite EG as a porous thermal conductive matrix material, is obtained by melt blending and hot pressing to obtain a flexible composite phase change material PW / SEBS / OBC / EG. The specific preparation method is as follows:
[0014] Step 1, placing a certain amount of expandable graphite powder in an alumina crucible, and performing heat treatment by microwave method to obtain expanded graphite EG; Step 2, placing a certain mass of paraffin in a beaker, heating it to completely melt it, adding a certain proportion of olefin block copolymer OBC, and continuously stirring it under certain conditions to completely melt and blend it to obtain a PW / OBC mixture; Step 3, adding a certain proportion of hydrogenated styrene-butadiene block copolymer SEBS to the PW / OBC mixture, and continuously stirring it under certain conditions to completely melt and blend it to obtain a PW / SEBS / OBC mixture; Step 4, adding a certain proportion of expanded graphite EG to the PW / SEBS / OBC mixture, and continuously stirring it under certain conditions to make it completely uniform to obtain a PW / SEBS / OBC / EG raw material; Step 5, placing the PW / SEBS / OBC / EG raw material in a mold, and pressing it under certain conditions to obtain a PW / SEBS / OBC / EG block, that is, to prepare a flexible composite phase change material.
[0015] The heat treatment conditions of the expandable graphite in step 1 are: continuous heating for 30 to 32 seconds at a heating power of 800W; the preparation conditions of the PW / OBC mixture in step 2 are: heating temperature of 160 to 170°C, stirring rate of 85 to 95rpm, and stirring time of 2 to 2.5h; the preparation conditions of the PW / SEBS / OBC mixture in step 3 are: heating temperature of 160 to 170°C, initial stirring rate of 50rpm, stirring rate increase rate of 50rpm / 10min, final stirring rate of 200rpm, and continuous stirring for 30 to 40min at the final stirring rate; in step 4, the stirring conditions are: stirring temperature of 160 to 170°C, stirring rate of 190 to 210rpm, and stirring time of 30 to 40min; in step 5, the hot pressing conditions are: the initial hot pressing temperature of 160 to 170°C, natural cooling to below 60°C, and hot pressing time of 30 to 40min.
[0016] The present invention has the following characteristics after DSC, planar thermal conductivity test, leakage test, bending test, etc.:
[0017] According to DSC test, the melting temperature of the PW / SEBS / OBC / EG flexible composite phase change material prepared by the present invention is between 62.06 and 63.54°C, and the melting enthalpy is between 124.84 and 136.14 J / g; the crystallization temperature is between 59.6 and 60.4°C, and the crystallization enthalpy is between 122.21 and 132.42 J / g;
[0018] The thermal conductivity test shows that the PW / SEBS / OBC / EG flexible composite phase change material prepared in the present invention has good thermal conductivity, and the thermal conductivity coefficient is between 3.07 and 4.54 W / (m·K);
[0019] The anti-leakage test shows that the PW / SEBS / OBC / EG flexible composite phase change material prepared in the present invention has good anti-leakage performance, and no obvious leakage occurs after 100 cycles at 80°C.
[0020] The bending test shows that the PW / SEBS / OBCEG flexible composite phase change material prepared by the present invention has good flexibility at the phase change temperature and does not break when bent.
[0021] At the same time, the present invention also protects the application of the flexible composite phase change material in solar thermoelectric power generation. The solar thermoelectric power generation system used includes a solar vacuum collector tube, a flexible composite phase change material, a thermoelectric power generation device and heat dissipation fins. The solar vacuum collector tube includes a glass outer tube 1 and a metal inner tube 6; the thermoelectric power generation device 3 and the flexible composite phase change material 2 are installed in sequence on the outer surface of the metal inner tube 6 facing the light; a selective absorption coating is coated on the outer surface of the flexible composite phase change material 2 to enhance the absorption of solar energy; an insulating layer 4 is covered on the end faces of the thermoelectric power generation device 3 and the flexible composite phase change material 2 to reduce heat loss; heat dissipation fins 5 are arranged in the area corresponding to the thermoelectric power generation device in the metal inner tube 6 to enhance the heat exchange between the cold end of the thermoelectric power generation device 3 and the cooling water in the metal inner tube 6, thereby improving the power generation performance.
[0022] The working process of the application system is as follows: when there is light, the solar radiation energy is first absorbed by the selective absorption coating on the surface of the flexible composite phase change material 2, converted into heat energy, and then absorbed and stored by the flexible composite phase change material 2. At the same time, the flexible composite phase change material 2 releases part of the heat energy to the thermoelectric power generation device 3 to drive it to output electrical energy to the outside. The waste heat of power generation is used to heat the cooling water in the metal inner tube 6 to achieve cogeneration of heat and power. When there is no light, the heat stored in the flexible composite phase change material 2 continuously provides heat energy to the thermoelectric power generation device 3 to maintain the thermoelectric power generation device 3 to continuously output electrical energy to the outside. The waste heat of power generation is used to heat the cooling water in the metal inner tube 6 to achieve cogeneration of heat and power. With the help of the heat storage function of the flexible composite phase change material and the power generation function of the thermoelectric power generation device, the application system enables the traditional solar water heater to have the characteristics of 24-hour continuous cogeneration of heat and power, and significantly improves the utilization rate of solar energy.
[0023] Therefore, the present invention has the following advantages over the prior art:
[0024] 1. The present invention cross-links SEBS and OBC to form a flexible network structure, which enhances packaging performance and mechanical properties. It can be bent according to application requirements and fit closely with other materials to improve heat transfer efficiency.
[0025] 2. Using EG as the thermal conductive matrix material to construct a continuous thermal conductive network, the composite material has a high thermal response rate, and the addition of EG enhances the material packaging performance and high compressive resistance;
[0026] 3. The preparation process of PW / SEBS / OBC / EG flexible composite phase change material is simple, the hot pressing time is short, it can be quickly formed, and it has excellent thermal stability and cycle stability;
[0027] 4. The PW / SEBS / OBC / EG flexible composite phase change material prepared by the present invention not only has a high thermal conductivity, the thermal conductivity coefficient of which is between 3.07 and 4.54 W / (m·K); it also has a high latent heat of phase change, the melting enthalpy is 124.84 to 136.14 J / g, and the crystallization enthalpy is 122.21 to 132.42 J / g;
[0028] 5. The application of the flexible composite phase change material described in the present invention in solar temperature difference power generation, with the help of the heat storage function of the flexible composite phase change material and the power generation function of the temperature difference power generation device, enables the traditional solar water heater to have 24-hour continuous cogeneration characteristics, significantly improving the utilization rate of solar energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Flow chart for the preparation of PW / SEBS / OBC / EG flexible composite phase change materials;
[0030] Figure 2 This is the principle diagram of the solar temperature difference power generation device;
[0031] Figure 3a and Figure 3b The melting process and crystallization process curves of DSC tests of Example 1, Example 2, Example 3 and Example 4 respectively;
[0032] Figure 4 Graphs of thermal conductivity of Example 1, Example 2, Example 3 and Example 4;
[0033] Figure 5 It is the anti-leakage test diagram of Example 1, Example 2, Example 3 and Example 4;
[0034] Figure 6 This is a bending test diagram of Example 1;
[0035] Figure 2 In the figure, 1-glass outer tube, 2-flexible composite phase change material, 3-temperature difference power generation device, 4-insulation layer, 5-heat dissipation fins, 6-metal inner tube. DETAILED DESCRIPTION
[0036] The method of the present invention is described below by means of specific examples and drawings, but the present invention is not limited thereto.
[0037] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0038] Example 1: Figure 1As shown, first, a certain amount of expandable graphite powder is taken, heated at a heating power of 800W for 30s for microwave heating expansion to obtain expanded graphite EG; then, 7g of paraffin wax PW is heated in a beaker at 160°C until it is completely melted, and then 0.3g of OBC is added, and the mixture is heated and stirred at a rate of 90rmp for 2h at 160°C to completely melt and blend, thereby obtaining a PW / OBC mixture; then, 1.2g of SEBS is added to the above-obtained PW / OBC mixture, and the mixture is stirred at 160°C with an initial stirring rate of 50rpm, a stirring rate increase rate of 50rpm / 10min, a final stirring rate of 200rpm, and stirring is continued for 32min at the final stirring rate to completely melt and blend, thereby obtaining PW / SEBS / OBC mixture; then, add 1.5g of EG to the above mixture, stir at 160°C, at a speed of 200rpm, for 35min until mixed evenly, to obtain expanded graphite / hydrogenated styrene-butadiene block copolymer / olefin block copolymer / paraffin composite phase change material, referred to as PW / SEBS / OBC-0.3 / EG raw material; finally, the flexible composite phase change material PW / SEBS / OBC / EG is naturally cooled to room temperature at an initial temperature of 160°C and then hot pressed for 38min. After hot pressing, a PW / SEBS / OBC / EG flexible composite phase change material block is obtained, referred to as PW / SEBS / OBC-0.3 / EG block.
[0039] Example 2: Figure 1As shown, first, a certain amount of expandable graphite powder is taken, heated at a heating power of 800W for 30s for microwave heating expansion to obtain expanded graphite EG; then, 7g of paraffin wax PW is heated in a beaker at 160°C until it is completely melted, and then 0.5g of OBC is added, and the mixture is heated and stirred at a rate of 85rmp for 2h at 160°C to completely melt and blend, thereby obtaining a PW / OBC mixture; then, 1.0g of SEBS is added to the above-obtained PW / OBC mixture, and the mixture is stirred at 162°C with an initial stirring rate of 50rpm, a stirring rate increase rate of 50rpm / 10min, a final stirring rate of 200rpm, and the mixture is stirred for 36min at the final stirring rate to completely melt. Blending to obtain a PW / SEBS / OBC mixture; then, adding 1.5 g of EG to the above mixture, stirring at 170°C, a stirring speed of 195 rpm, and a stirring time of 40 min until mixed evenly to obtain expanded graphite / hydrogenated styrene-butadiene block copolymer / olefin block copolymer / paraffin composite phase change material, referred to as PW / SEBS / OBC-0.3 / EG raw material; finally, the flexible composite phase change material PW / SEBS / OBC / EG is naturally cooled at an initial temperature of 161°C, and the hot pressing time is 39 min. After hot pressing molding, a PW / SEBS / OBC / EG flexible composite phase change material block is obtained, referred to as PW / SEBS / OBC-0.5 / EG block.
[0040] Example 3: Figure 1As shown, first, a certain amount of expandable graphite powder is taken, heated at a heating power of 800W for 30s for microwave heating expansion to obtain expanded graphite EG; then, 7g of paraffin wax PW is heated in a beaker at 170°C until it is completely melted, and then 0.6g of OBC is added, and the mixture is heated and stirred at a rate of 90rmp for 2.1h at 170°C to completely melt and blend, thereby obtaining a PW / OBC mixture; then, 0.9g of SEBS is added to the above-obtained PW / OBC mixture, and the mixture is stirred at 165°C with an initial stirring rate of 50rpm, a stirring rate increase rate of 50rpm / 10min, a final stirring rate of 200rpm, and continuous stirring for 40min at the final stirring rate to completely melt. The mixture was melt-blended to obtain a PW / SEBS / OBC mixture; then, 1.5 g of EG was added to the mixture, and the mixture was stirred at 163°C with a stirring speed of 206 rpm for 38 min until uniformly mixed to obtain an expanded graphite / hydrogenated styrene-butadiene block copolymer / olefin block copolymer / paraffin composite phase change material, referred to as PW / SEBS / OBC-0.3 / EG raw material; finally, the flexible composite phase change material PW / SEBS / OBC / EG was naturally cooled at an initial temperature of 170°C, and the hot pressing time was 34 min. After hot pressing, a PW / SEBS / OBC / EG flexible composite phase change material block was obtained, referred to as PW / SEBS / OBC-0.9 / EG block.
[0041] Example 4: Figure 1As shown in the figure, first, a certain amount of expandable graphite powder is taken, heated at a heating power of 800W for 30s for microwave heating expansion to obtain expanded graphite EG; then, 7g of paraffin wax PW is heated in a beaker at 170°C until it is completely melted, and then 1.0g of OBC is added, and the mixture is heated and stirred at a rate of 95rmp for 2.5h at 170°C to completely melt and blend, thereby obtaining a PW / OBC mixture; then, 0.5g of SEBS is added to the PW / OBC mixture obtained above, and the mixture is stirred at 170°C with an initial stirring rate of 50rpm, a stirring rate increase rate of 50rpm / 10min, a final stirring rate of 200rpm, and stirring is continued for 30min at the final stirring rate to completely melt and blend. Fully melt blending is performed to obtain a PW / SEBS / OBC mixture; then, 1.5 g of EG is added to the above mixture, and the mixture is stirred at 163°C, at a speed of 210 rpm, and for 30 min until it is evenly mixed to obtain an expanded graphite / hydrogenated styrene-butadiene block copolymer / olefin block copolymer / paraffin composite phase change material, referred to as PW / SEBS / OBC-1 / EG raw material; finally, the flexible composite phase change material PW / SEBS / OBC / EG is naturally cooled at an initial temperature of 163°C, and the hot pressing time is 30 min. After hot pressing molding, a PW / SEBS / OBC / EG flexible composite phase change material block is obtained, referred to as PW / SEBS / OBC-1 / EG block.
[0042] As shown in Figure 3, Figure 3a The melting process and crystallization process curves of the DSC tests of Example 1, Example 2, Example 3 and Example 4 are shown in FIG. Figure 3a It can be seen that during the melting process, the melting temperature is between 62.06 and 63.54 °C, and the melting enthalpy is between 124.84 and 136.14 J / g; Figure 3b It can be seen that the crystallization temperature is between 59.6 and 60.4 °C, and the crystallization enthalpy is between 122.21 and 132.42 J / g. Figure 4 As shown, in the thermal conductivity tests of Example 1, Example 2, Example 3 and Example 4, the smallest is Example 2, whose thermal conductivity is 3.07 W / (m·K), and the largest is Example 4, whose thermal conductivity is 4.54 W / (m·K). The thermal conductivity of pure paraffin is significantly improved, which greatly enhances the heat transfer rate.
[0043] like Figure 5 As shown, the leakage test diagram of Example 1, Example 2, Example 3 and Example 4 after cycling 100 times at 80°C. It can be seen from the figure that the flexible composite phase change material has a high retention rate of paraffin, and there is no obvious paraffin leakage, but there is a slight mark caused by the friction of expanded graphite on the surface of the filter paper.
[0044] like Figure 6As shown in the bending resistance test of Example 1, when the 2mm thick flexible composite phase change material is folded at 90° at 60°C, no obvious fracture is found, and the material can still maintain the bent state after cooling to room temperature, indicating that the material has good flexibility. Figure 2 As shown, the present invention also protects the application of flexible composite phase change materials in solar thermoelectric power generation. The applied solar thermoelectric power generation system includes a solar vacuum collector tube, a flexible composite phase change material, a thermoelectric power generation device and heat dissipation fins. The solar vacuum collector tube includes a glass outer tube 1 and a metal inner tube 6; on the outer surface of the metal inner tube 6 facing the light, a thermoelectric power generation device 3 and a flexible composite phase change material 2 are installed in sequence; a selective absorption coating is coated on the outer surface of the flexible composite phase change material 2 to enhance the absorption of solar energy; an insulating layer 4 is covered on the end faces of the thermoelectric power generation device 3 and the flexible composite phase change material 2 to reduce heat loss; heat dissipation fins 5 are arranged in the area corresponding to the thermoelectric power generation device in the metal inner tube 6 to enhance the heat exchange between the cold end of the thermoelectric power generation device 3 and the cooling water in the metal inner tube 6, thereby improving the power generation performance.
[0045] The working process of the application system is as follows: when there is light, the solar radiation energy is first absorbed by the selective absorption coating on the surface of the flexible composite phase change material 2, converted into heat energy, and then absorbed and stored by the flexible composite phase change material 2. At the same time, the flexible composite phase change material 2 releases part of the heat energy to the thermoelectric power generation device 3 to drive it to output electrical energy to the outside. The waste heat of power generation is used to heat the cooling water in the metal inner tube 6 to achieve cogeneration of heat and power. When there is no light, the heat stored in the flexible composite phase change material 2 continuously provides heat energy to the thermoelectric power generation device 3 to maintain the thermoelectric power generation device 3 to continuously output electrical energy to the outside. The waste heat of power generation is used to heat the cooling water in the metal inner tube 6 to achieve cogeneration of heat and power. With the help of the heat storage function of the flexible composite phase change material and the power generation function of the thermoelectric power generation device, the application system enables the traditional solar water heater to have the characteristics of 24-hour continuous cogeneration of heat and power, significantly improving the utilization rate of solar energy.
[0046] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A flexible composite phase change material, characterized in that: The flexible composite phase change material PW / SEBS / OBC / EG is prepared by melt blending with hydrogenated styrene-butadiene block copolymer SEBS as a flexible segment, olefin block copolymer OBC as a flexible elastomer, paraffin PW as a phase change material, and expanded graphite EG as a porous thermal conductive matrix material.
2. The flexible composite phase change material according to claim 1, characterized in that: The hydrogenated styrene-butadiene block copolymer SEBS, olefin block copolymer OBC and expanded graphite EG jointly play the role of shaping and packaging the phase change material to prevent leakage of the liquid phase change material.
3. The flexible composite phase change material according to claim 1, characterized in that: The material is provided with flexibility by adding hydrogenated styrene-butadiene block copolymer SEBS and olefin block copolymer OBC, and the material is provided with high thermal conductivity by adding expanded graphite EG.
4. The flexible composite phase change material according to claim 1, characterized in that: The flexible composite phase change material has a phase change temperature of 62.06-63.54°C, a phase change latent heat of 124.84-136.14 J / g, a crystallization temperature of 59.6-60.4°C, a crystallization enthalpy of 122.21-132.42 J / g, and a thermal conductivity of 3.07-4.54 W / (m·K).
5. The method for preparing a flexible composite phase change material according to claim 1, characterized in that: The following steps are involved: Step 1, placing a certain amount of expandable graphite powder in an alumina crucible, and performing heat treatment by microwave method to obtain expanded graphite EG; Step 2, placing a certain mass of paraffin wax in a beaker, heating it to completely melt it, adding a certain proportion of olefin block copolymer OBC, and continuously stirring it to completely melt and blend it to obtain a PW / OBC mixture; Step 3, adding a certain proportion of hydrogenated styrene-butadiene block copolymer SEBS to the PW / OBC mixture, and continuously stirring to completely melt and blend the mixture to obtain a PW / SEBS / OBC mixture; Step 4, adding a certain proportion of expanded graphite EG to the PW / SEBS / OBC mixture, stirring continuously to make it completely uniform, and obtaining a PW / SEBS / OBC / EG raw material; Step 5, placing the PW / SEBS / OBC / EG raw materials into a mold, performing hot pressing, and obtaining a PW / SEBS / OBC / EG block, that is, a flexible composite phase change material.
6. The preparation method according to claim 5, characterized in that: The heat treatment conditions of the expandable graphite powder in step 1 are: continuous heating for 30 to 32 seconds at a heating power of 800 W; the preparation conditions of the PW / OBC mixture in step 2 are: heating temperature of 160 to 170° C., stirring speed of 85 to 95 rpm, and stirring time of 2 to 2.5 h; the preparation conditions of the PW / SEBS / OBC mixture in step 3 are: heating temperature of 160 to 170° C., initial stirring speed of 50 rpm, and stirring speed increase rate of 50 rpm / 10 min , the final stirring rate is 200rpm, and stirring is continued for 30min-40min at the final stirring rate; in the step 4, the stirring conditions are as follows: the stirring temperature is 160-170°C, the stirring rate is 190-210rpm, and the stirring time is 30-40min; in the step 5, the hot pressing conditions are as follows: the PW / SEBS / OBC / EG raw materials are heated to a temperature of 160-170°C, naturally cooled to below 60°C for hot pressing, and the hot pressing time is 30-40min.
7. The preparation method according to claim 5, characterized in that: In the step 2, the mass ratio of paraffin wax PW to olefin block copolymer OBC is in the range of 70:3 to 70:10; in the step 3, the mass ratio of PW / OBC mixture to hydrogenated styrene-butadiene block copolymer SEBS is in the range of 73:12 to 80:5; in the step 4, the added amount of expanded graphite EG is 15% of the total mass of PW / SEBS / OBC / EG.
8. A solar temperature difference power generation system, characterized in that: The invention comprises a solar vacuum heat collecting tube, a temperature difference power generation device, a heat dissipation fin and the flexible composite phase change material as claimed in claim 1; the solar vacuum heat collecting tube comprises a glass outer tube (1) and a metal inner tube (6); the temperature difference power generation device (3) and the flexible composite phase change material (2) are sequentially installed on the outer surface of the metal inner tube (6) facing light; a selective absorption coating is coated on the outer surface of the flexible composite phase change material (2) to enhance the absorption of solar energy; the end surfaces of the temperature difference power generation device (3) and the flexible composite phase change material (2) are covered with a heat insulation layer (4) to reduce heat loss; heat dissipation fins (5) are arranged in the area of the metal inner tube (6) corresponding to the temperature difference power generation device to enhance the heat exchange between the cold end of the temperature difference power generation device (3) and the cooling water in the metal tube (6) to improve the power generation performance.
9. The solar temperature difference power generation system according to claim 8, characterized in that: When there is light, solar radiation energy is first absorbed by the selective absorption coating on the surface of the flexible composite phase change material (2), converted into heat energy, and then absorbed and stored by the flexible composite phase change material (2). At the same time, the flexible composite phase change material (2) releases part of the heat energy to the temperature difference power generation device (3) to drive it to output electrical energy to the outside. The waste heat from power generation is used to heat the cooling water in the metal inner tube (6), thereby realizing cogeneration of heat and power. When there is no light, the heat stored in the flexible composite phase change material (2) continuously provides heat energy to the temperature difference power generation device (3), maintaining the temperature difference power generation device (3) to continuously output electrical energy to the outside. The waste heat from power generation is used to heat the cooling water in the metal inner tube (6), thereby realizing cogeneration of heat and power.
10. The solar temperature difference power generation system according to claim 8, characterized in that: With the help of the heat storage function of the flexible composite phase change material and the power generation function of the temperature difference power generation device, the traditional solar water heater has the characteristics of 24-hour continuous cogeneration of heat and power, which significantly improves the utilization rate of solar energy.
Citation Information
Cited By
Self-healing full-spectrum self-adaptive flexible phase change material and preparation method thereof
CN119899639A
Novel double-wall material phase change elastic composite material and preparation method thereof
CN120349615A
High-temperature-regulation type weak-crosslinking stable-form phase-change elastomer material, preparation method thereof and application of elastomer material in modified asphalt
CN121991519A
